Light‐Emitting Diodes: An Organic Down‐Converting Material for White‐Light Emission from Hybrid LEDs (Adv. Mater. 43/2014). (November 2014) - Findlay, Neil J.; Bruckbauer, Jochen; Inigo, Anto R.; Breig, Benjamin; Arumugam, Sasikumar; Wallis, David J.; Martin, Robert W.; Skabara, Peter J.
<x xml:space="preserve">Abstract</x> Combining a yellow‐emitting organic material with a blue‐emitting inorganic light‐emitting device (LED) provides a hybrid white‐light LED. This approach, demonstrated by R. W. Martin, P. J. Skabara, and co‐workers on page 7290, couples very efficient blue emission with the flexibility, fast modulation speed, and cost effectiveness of the organic material. For the latter, BODIPY is used as the emitter and linked to a conjugated unit designed to efficiently absorb a suitable fraction of the blue light. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>